Dialychone, Jasmineira and Paradialychone (Annelida: Polychaeta: Sabellidae) from Japan and adjacent waters, including four new species descriptions - Nishi, Eijiroh; Tanaka, Katsuhiko; Tovar-Hernández, María Ana; Giangrande, Adriana (Zootaxa, 2009)
The genus Chone Krøyer, 1856, and related genera of the family Sabellidae (Polychaeta) are common members of softbottom communities. Four new species from Japanese waters are described herein: Dialychone okudai n. sp., from Hokkaido, Paradialychone katsuuraensis n. sp., from Katsuura, Boso Peninsula; P. edomae n. sp., from Tokyo Bay and Jasmineira kikuchii n. sp., from Ariake Sound, Kyushu. A re-description is also provided for a poorly known species C. cincta Zachs, 1933. This species, originally described from the Peter the Great Bay, Eastern Russia was recorded in this study from Amakusa and Ariake Sound, Kyushu and transferred to Paradialychone. Jasmineira kikuchii is the first record of the genus from Japan. The Japanese species described here are compared with other conspecifics of the world and a key for the sabellid genera with a glandular girdle on chaetiger 2 and thoracic acicular uncini is provided.